Does Green Investment Elevate CSR Performance? The Role of CSR Committee as Moderating Factor - Suhita Whini Setyahuni; Fakhmi Zakaria; Linda Ayu Oktoriza (Jurnal Akuntansi dan Perpajakan, 2023)
This study intends to investigate the effect of green investment and CSR committee on CSR performance. This study also analyzes the moderating effect of CSR committee on the relationship between green investment and CSR performance. We analyzed 117 firms-years observation from 39 companies listed in LQ-45 index from 2019-2021. Sample is selected using purposive sampling technique, which the availability of CSR information become the criteria of sample selection.  To test the hypotheses, we applied Moderated Regression Analysis (MRA). Our findings indicate that there is a positive impact of green investment and CSR committee on CSR performance. However, CSR committee does not play a moderating role in enhancing CSR performance. By using a new proxy of green investment and CSR performance measurement, our research contributes on providing a new insight on what factors influence the sustainability performance within legitimacy theory framework. Our findings provide empirical evidence that can be used by business practitioners and policymakers to consider the importance of independent CSR committee as a part of sustainability governance.